2015
DOI: 10.1038/nature15756
|View full text |Cite
|
Sign up to set email alerts
|

Tumour exosome integrins determine organotropic metastasis

Abstract: Ever since Stephen Paget’s 1889 hypothesis, metastatic organotropism has remained one of cancer’s greatest mysteries. Here we demonstrate that exosomes from mouse and human lung-, liver- and brain-tropic tumour cells fuse preferentially with resident cells at their predicted destination, namely lung fibroblasts and epithelial cells, liver Kupffer cells and brain endothelial cells. We show that tumour-derived exosomes uptaken by organ-specific cells prepare the pre-metastatic niche. Treatment with exosomes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
3,929
4
22

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,012 publications
(4,192 citation statements)
references
References 49 publications
68
3,929
4
22
Order By: Relevance
“…Furthermore, our analysis showed that proteins implicated in the processes of integrin‐mediated adhesion and mechanosensation were downregulated in the SDEs of patients with osteoporosis. Exosome binding by recipient cells is likely to be determined by a repertoire of integrins, which dictate exosome adhesion to specific cell types and ECM molecules (Hoshino et al., 2015). Among the DEPs of SDEs of osteoporosis patients, the β 1 and β 3 integrins and CD34 were representatives of the downregulated proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our analysis showed that proteins implicated in the processes of integrin‐mediated adhesion and mechanosensation were downregulated in the SDEs of patients with osteoporosis. Exosome binding by recipient cells is likely to be determined by a repertoire of integrins, which dictate exosome adhesion to specific cell types and ECM molecules (Hoshino et al., 2015). Among the DEPs of SDEs of osteoporosis patients, the β 1 and β 3 integrins and CD34 were representatives of the downregulated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Hoshino et al. (2015) demonstrated that, in addition to adhesive properties, exosomal integrin uptake can activate SRC in specific resident cells. SRC is an upstream signaling partner of ERK and regulates SMAD nuclear translation through activation of osterix and results in osteoblastic bone mineralization (Choi et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular origin of an EV can guide its surface-expressed proteins, intrinsic targeting properties, and target cell tropism. For example, Hoshino et al reported that tumour cell-derived exosomes display different integrins depending on the tumour origin, and these proteins mediate tumour metastasis to specific organ sites; exosomes expressing ITGαvβ5 specifically bind to Kupffer cells and thus mediate liver tropism, whereas exosomal ITGα6β4 and ITGα6β1 bind lung-resident fibroblasts and epithelial cells to govern lung tropism [84]. Another study showed that tetraspanin-associated receptors on exosomal membranes can play an important role in target cell selection, as exosomes containing tetraspanin–integrin complexes (span8–integrin α4 complexes) could target CD54-expressing endothelial and pancreatic cells [85].…”
Section: Therapeutic Applications Of Surface-modified Evsmentioning
confidence: 99%
“…tetraspanins and flotillins) as well as coding and non-coding RNAs (including microRNAs), and different types of lipids [1,35]. The molecular organisation of their surface provides a kind of address code allowing them to selectively interact with specific target cells [6,7]. Thus, depending on their origin and their cargo, EVs can exert specific functions.…”
Section: Introductionmentioning
confidence: 99%